A Conversation with Ernest R. Forbes

(untitled) (The Department of History at the University of New Brunswick, 2012)
Ernest R. (Ernie) Forbes needs no elaborate introduction to readers of this journal. Distinguished historian and long-serving member of the Department of History at the University of New Brunswick until his retirement in 2001, he authored the lead article in the very first issue of Acadiensis (Autumn/automne 1971) and subsequently became a frequent contributor. He has served continuously on the journal’s Editorial Board since 1974. This “Conversation” is offered in honour of the Spring 2012 publication by Acadiensis Press of The Education of an Innocent: An Autobiography by E.R. “Ernie” Forbes (in which this “Conversation” also appears).